2012
DOI: 10.1111/j.1467-9957.2012.02302.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Development on Poverty and Inequality in African Countries*

Abstract: Understanding the factors that are important in determining poverty and inequality is one of the steps in the fight to eradicate poverty in the world. This is particularly so for African countries because when compared to other regions, Africa has the largest concentration of people living below the poverty line. This article examines the effect of financial development as measured by private credit and broad money (M2) on poverty and inequality in African countries. The empirical results indicate that financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 51 publications
3
20
0
1
Order By: Relevance
“…A positive relationship exists between FDI and poverty reduction in the long run and the short run; it is supported by theory where the inflow of FDI increase is essential in stimulating the production of goods and services in an economy and creates more jobs. The results of (Fowowe & Shuaibu, 2014, Fowowe & Abidoye, 2013, Gohou & Soumare, 2012, and findings of Zaman et al, 2012a are supported in our study. The FDI and poverty found significant but low coefficient in the context of Pakistan.…”
Section: Estimation Of the Ardl Model And Robustnesssupporting
confidence: 92%
See 1 more Smart Citation
“…A positive relationship exists between FDI and poverty reduction in the long run and the short run; it is supported by theory where the inflow of FDI increase is essential in stimulating the production of goods and services in an economy and creates more jobs. The results of (Fowowe & Shuaibu, 2014, Fowowe & Abidoye, 2013, Gohou & Soumare, 2012, and findings of Zaman et al, 2012a are supported in our study. The FDI and poverty found significant but low coefficient in the context of Pakistan.…”
Section: Estimation Of the Ardl Model And Robustnesssupporting
confidence: 92%
“…The theoretical guidance has been providing by the arguments as mentioned above that the relationship between FDI and poverty reduction with some controlled variables. Since the studies of Fowowe and Shuaibu (2014), Fowowe and Abidoye (2013) and Gohou and Soumare (2012) have explored the connection between FDI and poverty reduction. Our study based on Pakistan economy and differs from the prior studies, which are based on poverty measure using the poverty line decided by 2350 calories.…”
Section: Theoretical Framework and The Empirical Modelmentioning
confidence: 99%
“…Inoue and Hamori () find similar results considering credit in a panel of 28 Indian States. By contrast, Guillaumont‐Jeanneney and Kpodar () and Fowowe and Abidoye () conclude that the association between private credit and poverty turns out to be statistically insignificant.…”
Section: Theoretical Background and Review Of The Literaturementioning
confidence: 94%
“…The empirical studies showed that some researchers used the poverty headcount ratio at $1, 1.25, or 2 per day as a proxy for poverty (see Levine 2004, 2007;Patrick Honohan 2004;Takeshi Inoue and Shigeyuki Hamori 2010;Sylviane Guillaumont Jeanneney and Kangni Kpodar 2011;Salvador Perez-Moreno 2011;and Fowowe and Abidoye 2013). Other works used private consumption per capita, growth of income, and changes in the distribution of income as a proxy for poverty (see Hossein Jalilian and Colin Kirkpatrick 2005;Beck, Demirgüç-Kunt, and Levine 2007;Ejaz Ahmad Azra, Dilawar Khan, and Waheed Ullah Jan 2012;Leila Chemli 2014;and Gazi Salah Uddin et al 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, there has been a near consensus on the selection of financial development indicator. Most studies used private credit as percent GDP as a proxy for financial development Levine 2004, 2007;Honohan 2004;Jalilian and Kirkpatrick 2005;Inoue and Hamori 2010;Jeanneney and Kpodar 2011;Azra, Khan, and Jan 2012;Fowowe and Abidoye 2013;and Chemli 2014). In the present work, we also used domestic credit to private sector as percent GDP considering the related literature, as well as stock market capitalization as percent of GDP.…”
Section: Literature Reviewmentioning
confidence: 99%